Composite monofilament, its preparation method and application, and high current density single-walled carbon nanotube macro-fiber superconducting alternative motor winding

CN122930652APending Publication Date: 2026-10-16EXTREME LIGHT POWER (BEIJING) TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611260022.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

铜绕组电机存在以下固有缺陷:重量大、电流密度受限、趋肤效应损耗以及热管理困难,为突破铜绕组的电流密度瓶颈,高温超导电机采用稀土钡铜氧(REBCO)带材作为绕组材料

Benefits of technology

1.室温超导替代效应:通过单壁碳纳米管宏观纤维的弹道输运特性和铜层导电增强,在室温下实现3×108~5×108A/m2量级的极限载流能力,达到HTS材料工程电流密度的同一数量级,虽连续工作电流密度受焦耳热约束(5~25A/mm2),但完全不需要低温冷却系统,从根本上消除了HTS电机的最大技术瓶颈;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930652A_ABST
    Figure CN122930652A_ABST
Patent Text Reader

Abstract

The application provides a composite monofilament and a preparation method and application thereof, and a high current density single-wall carbon nanotube macroscopic fiber superconducting alternative motor winding, and belongs to the technical field of motor winding manufacturing. The composite monofilament comprises, from inside to outside, a conductive core layer, an inner layer heat-conducting transition layer, an intermediate electric insulation layer and an outer layer heat-resistant protection layer, and takes the single-wall carbon nanotube macroscopic fiber as a core and a copper layer as a shell. The application reaches the same order of magnitude of the HTS material engineering current density through the ballistic transport characteristics of the SWCNT macroscopic fiber and the electric conduction enhancement of the copper layer, fundamentally eliminates the maximum technical bottleneck of the HTS motor without a low-temperature cooling system, and realizes self-heat dissipation operation through the self-heat dissipation path of the axial heat conduction-end heat dissipation of the core layer by using the high axial thermal conductivity of the SWCNT macroscopic fiber. The prepared high current density single-wall carbon nanotube macroscopic fiber superconducting alternative motor winding is applied to the fields of aerospace motors and electric vehicle driving motors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of motor winding manufacturing technology, and in particular to a composite monofilament, its preparation method and application, and a high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding. Background Technology

[0002] Currently, copper wire is commonly used as the conductive material in motor windings. Copper-winded motors have inherent drawbacks: heavy weight, limited current density, skin effect losses, and difficulties in thermal management. To overcome the current density bottleneck of copper windings, high-temperature superconducting motors use rare-earth barium copper oxide (REBCO) tape as the winding material. REBCO material can achieve superconductivity in the liquid nitrogen temperature range (77K), with an engineering critical current density reaching 400 A / mm². 2 Above (77K, self-field). However, in high magnetic field motor applications, REBCO usually needs to operate at 20~40K to maintain sufficient critical current. High temperature superconducting (HTS) motor windings have the following fundamental defects: (1) Low temperature dependence: High field HTS motors need to operate in a low temperature environment of 20~40K, requiring liquid nitrogen or cold helium gas circulation cooling system, the cost of which accounts for about 35% of the total cost of the motor; (2) Superconducting risk: The superconducting state suddenly disappears (superconducting) when the temperature, magnetic field or current exceeds the critical value, resulting in a sharp increase in resistance, which may burn out the winding. The response time of the superconducting protection circuit needs to be within 40ms, and the system complexity is extremely high; (3) Material reliability challenge: REBCO tape is prone to micro-cracks under mechanical vibration and thermal cycling conditions; (4) High cost: The cost of HTS tape accounts for more than 25% of the total cost of the motor. In recent years, carbon nanotube (CNT) fibers have attracted attention as a new type of lightweight conductive material. Existing CNT conductor insulation layers mostly use a single polymer coating, without considering the multi-physical field coupling requirements of motor windings in high-temperature, high-frequency, and strong magnetic field environments. Summary of the Invention

[0003] In view of this, the purpose of this invention is to provide a composite monofilament, its preparation method and application, and a high-current-density single-walled carbon nanotube macroscopic fiber superconducting alternative to motor windings. The composite monofilament provided by this invention is suitable for high-temperature, high-frequency, and strong magnetic field environments.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a composite monofilament comprising, from the inside out, a conductive core layer, an inner thermally conductive transition layer, an intermediate electrically insulating layer, and an outer heat-resistant protective layer. The conductive core layer has a core-shell structure, with a single-walled carbon nanotube (SWCNT) macrofiber as the core and a copper layer as the shell.

[0005] Preferably, an interface transition layer is further provided between the macroscopic fibers of the single-walled carbon nanotubes and the copper layer, and the material of the interface transition layer includes Ti and / or Al.

[0006] Preferably, the inner thermally conductive transition layer includes a thermally conductive substrate and a thermally conductive filler, and the content of the thermally conductive filler in the inner thermally conductive transition layer is 10~30wt%.

[0007] Preferably, the intermediate electrical insulating layer comprises polyimide and / or fluorinated ethylene propylene copolymer.

[0008] Preferably, the outer heat-resistant protective layer is a polyamide-imide layer containing silica or a polyether ether ketone layer containing boron nitride.

[0009] This invention also provides a method for preparing the composite monofilament described in the above technical solution, comprising the following steps: Provides macroscopic fibers of single-walled carbon nanotubes; Physical vapor deposition (PVD) is performed on the surface of the single-walled carbon nanotube macrofiber to form the copper layer, thus obtaining the conductive core layer. The conductive core layer is sequentially combined with an inner thermally conductive transition layer, an intermediate electrical insulating layer, and an outer heat-resistant protective layer to obtain the composite monofilament.

[0010] The present invention also provides the application of the composite monofilament described in the above technical solution or the composite monofilament prepared by the above technical solution as a conductive material in the field of motors.

[0011] The present invention also provides a high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding, which is formed by multi-stage stranding of composite monofilaments as described in the above technical solution or composite monofilaments prepared by the above technical solution, wherein the number of stranding stages is ≥2 and the stranding directions of adjacent stages are opposite.

[0012] Preferably, the number of twisting stages in the multi-stage twisting is 3.

[0013] Preferably, the diameter d1 of the outermost composite monofilament of the high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding satisfies Formula 1: Formula 1; Where δ is the skin depth in meters (m), ρ is the macroscopic fiber resistivity of single-walled carbon nanotubes in Ω·m, μ0 is the vacuum permeability in H / m, f is the alternating current frequency in Hz, and d1 is in meters (m).

[0014] The present invention provides a composite monofilament comprising, from the inside out, a conductive core layer, an inner thermally conductive transition layer, an intermediate electrically insulating layer, and an outer heat-resistant protective layer. The conductive core layer has a core-shell structure, with a single-walled carbon nanotube macrofiber as the core and a copper layer as the shell.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Room-temperature superconducting substitution effect: By leveraging the ballistic transport properties of macroscopic fibers in single-walled carbon nanotubes and the enhanced conductivity of the copper layer, 3×10⁻⁶ superconducting nanotubes were achieved at room temperature. 8 ~5×10 8 A / m 2 The ultimate current-carrying capacity is on the same order of magnitude as the engineering current density of HTS materials, although the continuous operating current density is constrained by Joule heating (5~25A / mm). 2 However, it does not require a low-temperature cooling system at all, fundamentally eliminating the biggest technical bottleneck of HTS motors; 2. Structural elimination of skin effect: Through the matching design of multi-level stranding structural parameters and the skin depth of macroscopic fibers of single-walled carbon nanotubes, each composite filament is in the effective conductive region. The AC loss is much lower than that of copper windings under high-frequency conditions of 10~100kHz, which is especially suitable for high-speed motors. 3. Self-heating winding architecture: Utilizing the high axial thermal conductivity of single-walled carbon nanotube macrofibers, a self-heating path is designed with axial heat conduction in the core layer and end heat dissipation. After copper plating, the conductive core layer achieves a conductivity of 5 A / mm². 2 The lower Joule heat power density of copper is 10 A / mm². 2 It is 0.97 times lower than the previous level, enabling self-heating operation; 4. Gradient insulation composite method: The three-layer gradient insulation structure, consisting of an inner thermally conductive layer, a middle insulating layer, and an outer heat-resistant layer (when the outer heat-resistant protective layer is a polyamide-imide layer containing silica, it also has corona resistance), solves the three core problems of thermal management, electrical insulation, and corona resistance at the same time, while existing CNT wires only use a single insulation layer; 5. Integrated Conductivity Enhancement and Protection with Copper Layer: A copper layer is formed on the surface of single-walled carbon nanotube macrofibers, creating a CNT-Cu core-shell structure. This copper layer provides a highly conductive surface pathway (effective conductivity 1.0 × 10⁻⁶). 7 ~3.0×10 7 The copper layer significantly reduces the overall resistance of the fiber (S / m) and acts as a protective layer to prevent oxidation and mechanical damage to the SWCNT core layer. Compared with the traditional iodine doping scheme, the copper layer does not have the problem of high-temperature desorption and degradation of dopants (the conductivity of CNT-Cu core-shell fiber decreases by <5% after aging at 200℃ for 1000 hours), and the copper layer can further form a good interfacial bond with the outer insulation system. 6. High slot fill factor rectangular forming: Through the rolling process after the third-stage forming and stranding, the winding wire cross section is formed into a rectangle, and the slot fill factor can reach 72~82%, which is 10~20% higher than that of traditional round copper wire. Under the same slot area, the winding ampere-turns can be increased, and the motor torque density can be improved. 7. Weight Advantage: The CNT-Cu core-shell fiber density is 2.0~3.5 g / cm3 (depending on the copper layer thickness), which is still only 22~39% of the density of copper. While introducing additional weight, the copper layer provides highly conductive surface pathways (effective conductivity is close to 1 / 6~1 / 2 of copper). In applications where 3~4 times the copper winding loss is acceptable, the total winding weight can be reduced to 40~46% of that of copper windings, making it suitable for lightweight applications such as aerospace and drones where weight is highly sensitive and higher losses are acceptable. 8. No quench risk: Unlike HTS windings, the conductivity of SWCNT fibers does not depend on the phase transition state, and there is no risk of a sudden increase in resistance due to quench. The system safety and reliability are significantly better than HTS motors.

[0016] The present invention also provides a method for preparing the composite monofilament described in the above technical solution. The preparation method of the present invention is simple to operate and suitable for industrial application. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the cross-sectional structure of the composite monofilament described in this invention; Figure 2 This is a flowchart of the multi-stage twisting process of the present invention; Figure 3 SEM image of the macroscopic fibers of SWCNT obtained in Example 1; Figure 4 This is a SEM image of the conductive core layer obtained in Example 1. Detailed Implementation

[0018] The present invention provides a composite monofilament comprising, from the inside out, a conductive core layer, an inner thermally conductive transition layer, an intermediate electrically insulating layer, and an outer heat-resistant protective layer. The conductive core layer has a core-shell structure, with a single-walled carbon nanotube macrofiber as the core and a copper layer as the shell.

[0019] Figure 1 This is a schematic diagram of the cross-sectional structure of the composite monofilament described in this invention.

[0020] Unless otherwise specified, all raw materials used in this invention are commercially available products in the field or are obtained using conventional technical means in the field.

[0021] The composite monofilament of the present invention includes a conductive core layer with a core-shell structure, using a single-walled carbon nanotube macrofiber as the core and a copper layer as the shell. The copper layer can improve the conductivity and remain stable within the motor operating temperature range (-40℃~180℃), without any doping desorption degradation problem. Furthermore, the copper layer can protect the single-walled carbon nanotube macrofiber from environmental oxidation and mechanical wear.

[0022] In this invention, the conductivity of the conductive core layer preferably decreases by less than 5% after aging at 200°C for 1000 hours.

[0023] In this invention, the conductivity of the conductive core layer is preferably 1.0 × 10⁻⁶. 7 ~3.0×10 7 S / m.

[0024] In this invention, the preferred parameters of the macroscopic single-walled carbon nanotube fibers include: diameter: 10~50 μm; electrical conductivity: 5.0 × 10⁻⁶. 6 ~7.0×10 6 S / m; Current carrying capacity (limited ampacity): 3.0 × 10 8 ~5.0×10 8 A / m 2 Tensile strength: 800~1200MPa; Density: 1.2~1.8g / cm³ 3 Orientation factor (Herman factor): ≥0.985.

[0025] In this invention, the single-walled carbon nanotube macrofibers are preferably prepared using a liquid crystal wet spinning process, which includes the following steps: SWCNT powder was dispersed in chlorosulfonic acid to obtain a liquid crystal phase spinning solution; The liquid crystal phase spinning solution is wet-spun to obtain the macroscopic fiber of single-walled carbon nanotubes.

[0026] In this invention, the purity of the SWCNT powder is preferably >92wt%, specifically 93wt%, 95wt% and 97wt%, and the metal catalyst residue is preferably <0.9wt%, specifically 0.8wt%, 0.5wt% and 0.3wt%.

[0027] In this invention, the concentration of SWCNT in the liquid crystal phase spinning solution is preferably 0.5~5.0wt%, specifically 3wt%.

[0028] In this invention, the liquid crystal phase spinning solution is preferably extruded into a coagulation bath through a porous spinneret, and continuous SWCNT fibers are formed through double diffusion coagulation to obtain the macroscopic fibers of single-walled carbon nanotubes.

[0029] In this invention, the coagulation bath preferably comprises an acetone solution.

[0030] In this invention, after forming the continuous SWCNT fibers, it is preferable to further densify them by air-segment gravity traction to improve orientation and density, thereby obtaining the macroscopic fibers of single-walled carbon nanotubes.

[0031] In this invention, the thickness of the copper layer is preferably 50nm~5μm, specifically 1.5, 2 or 3μm, and the thickness of the copper layer preferably does not exceed 50% of the radius of the SWCNT fiber, specifically 6%, 16% or 17%, to ensure the lightweight main position of the conductive core layer.

[0032] In this invention, an interface transition layer is preferably provided between the macroscopic single-walled carbon nanotube fiber and the copper layer. The material of the interface transition layer preferably includes Ti and / or Al. The interface transition layer forms a chemical bonding interface with the oxygen-containing functional groups on the SWCNT surface, and a diffusion interface is formed during the annealing stage of the preparation process, which further improves the bonding strength between the copper layer and the SWCNT fiber.

[0033] In this invention, the thickness of the interface transition layer is preferably 10~50nm.

[0034] In this invention, the conductive core layer is preferably prepared by a method comprising the following steps: Provides macroscopic fibers of single-walled carbon nanotubes; The copper layer is formed by physical vapor deposition on the surface of the single-walled carbon nanotube macrofiber, thus obtaining the conductive core layer.

[0035] The present invention preferably pre-treats the single-walled carbon nanotube macrofibers with plasma to obtain pre-treated single-walled carbon nanotube macrofibers, and then performs the magnetron sputtering.

[0036] In this invention, the plasma pretreatment is preferably Ar ion cleaning, the bias voltage of the Ar ion cleaning is preferably -50~-150V, more preferably -100V, the Ar gas flow rate is preferably 50~80sccm, more preferably 60sccm, and the time is preferably 10~20min, more preferably 15min. The function of the plasma pretreatment is to remove adsorbates on the fiber surface and activate oxygen-containing functional groups (hydroxyl, carboxyl, etc.) on the surface, providing nucleation sites for copper atom deposition and improving the adhesion of the copper layer.

[0037] In this invention, the physical vapor deposition is preferably magnetron sputtering, and the magnetron sputtering preferably includes sequential magnetron sputtering of the interface transition layer and magnetron sputtering of the copper layer.

[0038] In this invention, the parameters for magnetron sputtering of the interface transition layer preferably include: DC power of 50~150W and deposition rate of 2~10nm / min.

[0039] In this invention, the preferred parameters for the copper layer magnetron sputtering include: using a high-purity copper target (purity ≥ 99.99 wt%) as the sputtering source, argon as the working gas, a working gas pressure of 0.3~0.8 Pa (specifically 0.5 Pa), a DC power of 100~300 W (specifically 150 or 200 W), a sample holder rotating at 5~20 rpm (specifically 5, 10 or 15 rpm) to ensure uniform circumferential deposition of the copper layer, and a deposition rate of 50~200 nm / min (specifically 80, 100 or 120 nm / min).

[0040] After the magnetron sputtering is completed, the present invention preferably performs annealing. The annealing is preferably carried out in a vacuum or inert atmosphere. The annealing temperature is preferably 300~500℃, more preferably 350 or 400℃, and the annealing time is preferably 30~60min. The purpose of the annealing is to promote the diffusion of Cu atoms into the gap between the SWCNT tube bundles, reduce the inter-tube contact resistance, eliminate sputtering stress, and improve the density of the copper layer.

[0041] In this invention, the inert atmosphere preferably includes argon.

[0042] The composite monofilament of the present invention includes an inner thermally conductive transition layer, which has both radial heat diffusion and primary electrical insulation functions. It establishes a radial heat conduction channel between the conductive core layer and the intermediate electrical insulation layer, so as to quickly conduct the Joule heat inside the winding to the outer layer for dissipation.

[0043] In this invention, the thickness of the inner thermally conductive transition layer is preferably 2~10μm, specifically 5, 8 or 10μm, and the thermal conductivity is preferably 2~20W / m·K in the in-plane (along the fiber axis) and 0.5~1.5W / m·K in the radial (through the surface) direction.

[0044] In this invention, the inner thermally conductive transition layer preferably includes a thermally conductive substrate and a thermally conductive filler, and the content of the thermally conductive filler in the inner thermally conductive transition layer is preferably 10-30 wt%, more preferably 10 wt%, 15 wt%, or 20 wt%.

[0045] In this invention, the thermally conductive substrate preferably includes polyimide (PI) or polyether ether ketone (PEEK), wherein the polyimide is a heat-insulating polymer with temperature resistance (decomposition temperature > 500℃), flexibility, and insulation properties.

[0046] In this invention, the thermally conductive filler preferably comprises boron nitride nanosheets (BNNP), and the boron nitride nanosheets preferably comprise hexagonal boron nitride nanosheets.

[0047] When the thermally conductive substrate is preferably polyimide, the inner thermally conductive transition layer is preferably prepared by dip-coating-curing method, which preferably includes the following steps: dipping a thermally conductive insulating composite slurry onto the surface of the conductive core layer at a linear velocity of 10~50 mm / s (specifically 20 mm / s), and then curing it at 200~350℃ (specifically 300℃) for 10~60s (specifically 30s) to obtain polyimide, thus forming the inner thermally conductive transition layer; the thermally conductive insulating composite slurry preferably includes a polyimide precursor, a thermally conductive filler, and water, and the polyimide precursor preferably includes polyamic acid (PAA).

[0048] When the thermally conductive matrix is ​​preferably polyetheretherketone, the inner thermally conductive transition layer is preferably obtained by extrusion. The extrusion method preferably includes the following steps: extruding the thermally conductive insulating composite material on the surface of the conductive core layer. The thermally insulating composite material preferably includes polyetheretherketone and thermally conductive filler. The extrusion temperature is preferably 360~400℃. The extrusion process also preferably includes cooling and shaping.

[0049] The composite monofilament of the present invention includes an intermediate electrical insulation layer, which provides primary insulation, as well as winding-to-ground insulation and turn-to-turn insulation.

[0050] In this invention, the intermediate electrical insulating layer preferably comprises polyimide and / or fluorinated ethylene propylene copolymer (perfluoroethylene propylene copolymer, polyperfluoroethylene propylene, FEP).

[0051] In this invention, when the intermediate electrical insulating layer is polyimide, the intermediate electrical insulating layer is of high temperature resistance type, the polyimide is preferably a thin film wrapping layer, the thickness is preferably 5~20μm, specifically 10μm, the temperature resistance level is preferably ≥220℃, and the dielectric strength is preferably ≥200kV / mm.

[0052] In this invention, the polyimide is preferably prepared by dip-coating-curing method, which preferably includes the following steps: dipping an aqueous solution of polyamic acid onto the surface of the inner thermally conductive transition layer at a linear velocity of 10-50 mm / s, and then curing it at 200-350°C for 10-60 s to obtain polyimide.

[0053] In this invention, when the intermediate electrical insulating layer is a fluorinated ethylene propylene copolymer, the intermediate electrical insulating layer is of the high-frequency low-loss type. The fluorinated ethylene propylene copolymer is preferably an extruded coating layer with a thickness of 10~30μm, specifically 10, 15 or 20μm. The dielectric constant is preferably 2.0~2.1 (1MHz), and the dielectric loss tangent is preferably <0.0003. It is suitable for high-speed motors with operating frequencies >1kHz.

[0054] In this invention, the fluorinated ethylene propylene copolymer is preferably obtained by extrusion, the extrusion temperature is preferably 330~380°C, and water cooling curing is preferably included after the extrusion is completed.

[0055] In this invention, when the intermediate electrical insulating layer comprises both polyimide and fluorinated ethylene propylene copolymer, it is preferable to provide polyimide on the surface of the inner thermally conductive transition layer to provide a heat-resistant skeleton, and to provide fluorinated ethylene propylene copolymer on the surface of the polyimide to provide high-frequency insulation and water tightness.

[0056] The composite monofilament of the present invention includes an outer heat-resistant protective layer, which provides high temperature resistance, corona resistance and mechanical protection, as well as environmental aging resistance.

[0057] In this invention, the thickness of the outer heat-resistant protective layer is preferably 5~15μm, specifically 8, 10 or 12μm.

[0058] In this invention, the corona resistance life of the outer heat-resistant protective layer under a field strength of 50Hz and 20kV / mm is preferably ≥100h.

[0059] In this invention, the outer heat-resistant protective layer is preferably a polyamide-imide layer containing silicon dioxide or a polyether ether ketone layer containing boron nitride.

[0060] In this invention, the silica content in the silica-containing polyamide-imide layer is preferably 5 to 15 wt%, specifically 8 wt% or 10 wt%.

[0061] In this invention, the particle size of the silicon dioxide is preferably 20-50 nm. In this invention, the boron nitride content in the boron nitride-containing polyether ether ketone layer is preferably 10-20 wt%.

[0062] When the outer heat-resistant protective layer is preferably a polyamide-imide layer containing silica, it is preferably prepared by a coating-curing method, which preferably includes the following steps: coating the surface of the intermediate electrical insulating layer with the outer heat-resistant protective layer slurry, and then curing it at 200°C for 60 seconds to form the outer heat-resistant protective layer, thereby obtaining the composite monofilament.

[0063] When the outer heat-resistant protective layer is preferably a boron nitride-containing polyether ether ketone layer, it is preferably obtained by extrusion. The extrusion method preferably includes the following steps: extruding the boron nitride-containing polyether ether ketone onto the surface of the intermediate electrical insulating layer, the extrusion temperature is preferably 360~400℃, and the extrusion process preferably includes cooling and shaping.

[0064] This invention also provides a method for preparing the composite monofilament described in the above technical solution, comprising the following steps: Provides macroscopic fibers of single-walled carbon nanotubes; The copper layer is formed by magnetron sputtering of the surface of the single-walled carbon nanotube macrofiber to obtain the conductive core layer. The conductive core layer is sequentially combined with an inner thermally conductive transition layer, an intermediate electrical insulating layer, and an outer heat-resistant protective layer to obtain the composite monofilament.

[0065] The present invention will not describe the preparation method again, but it is preferable to follow the preparation method of the conductive core layer, the inner thermally conductive transition layer, the intermediate electrical insulating layer and the outer heat-resistant protective layer.

[0066] The present invention also provides the application of the composite monofilament described in the above technical solution or the composite monofilament prepared by the above technical solution as a conductive material in the field of motors.

[0067] The present invention also provides a high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding, which is formed by multi-stage stranding of composite monofilaments as described in the above technical solution or composite monofilaments prepared by the above technical solution, wherein the number of stranding stages is ≥2 and the stranding directions of adjacent stages are opposite.

[0068] This invention systematically optimizes the high-frequency skin effect, proximity effect, slot fill factor and bending fatigue of motor windings, and designs a multi-stage stranding structure.

[0069] In this invention, the number of stranding stages of the multi-stage stranding is preferably 3, specifically including a first-stage stranding, a second-stage stranding, and a third-stage stranding. Figure 2 This is a flowchart of the multi-stage twisting process of the present invention.

[0070] In this invention, the first-stage stranding preferably includes the following steps: taking N1 composite monofilaments and stranding them with a twist pitch P1 and a twist direction D1 to form a primary strand. The first-stage stranded composite monofilaments are subjected to uniform stress and have a regular shape, which can weaken the high-frequency skin effect and make the wire soft and resistant to bending.

[0071] In this invention, the parameters of the first-stage twisting preferably include: N1 = 7, 19 or 37 (preferably corresponding to 1+6, 1+6+12, 1+6+12+18 structures respectively). The twist pitch P1 = 8~20 times the diameter of the composite monofilament, specifically 15; Twist direction D1 = Z direction (right-handed).

[0072] In this invention, the diameter of the primary strand is preferably 0.15~0.8mm.

[0073] In this invention, the second-stage stranding preferably includes the following steps: taking N2 primary strands and stranding them with a twist pitch P2 and a twist direction D2 to form a secondary cable. The positive and negative twist directions of the second-stage stranding offset the primary torsional stress, so the cable does not twist and is straight and easy to process.

[0074] In this invention, the parameters of the second-stage twisting preferably include: N2 = 7, 12, or 19 roots; The twist pitch P2 is 10 to 25 times the diameter of the primary strand, specifically 12; The twist direction D2 = S direction (left-handed), which is opposite to the first stage twisting direction, to achieve torque balance.

[0075] In this invention, the diameter of the secondary cable is preferably 0.5 to 3.0 mm.

[0076] In this invention, the third-stage stranding preferably includes the following steps: taking N3 secondary cables and stranding them with a twist pitch P3 and a twist direction D3 to form the high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding. The third-stage stranding further improves flexibility, adapts to wire bending, and can balance residual torque again. The multi-subdivided conductor reduces high-frequency loss, and the irregular cross-section significantly improves the slot fill factor, resulting in better heat dissipation and higher motor power.

[0077] In this invention, the parameters of the third-stage twisting preferably include: N3 = 4 to 12 (specifically, it can be 6, 8, or 12). The twist pitch P3 is 15 to 30 times the diameter of the secondary cable, specifically 20; Twist direction D3 = Z direction (right-handed).

[0078] In this invention, the cross-section of the high current density single-walled carbon nanotube macro-fiber superconducting alternative motor winding is preferably circular or rolled into a rectangle or trapezoid to improve the slot fill factor.

[0079] In this invention, the width-to-thickness ratio of the rectangle is preferably 1:1 to 4:1, more preferably 1.48:1, 1.49:1 or 2:1.

[0080] In this invention, the slot fill factor is preferably 72-82% (compared to only 60-65% for traditional round copper wire).

[0081] In this invention, the diameter d1 of the outermost composite monofilament of the high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding preferably satisfies Formula 1: Formula 1; Where δ is the skin depth in meters (m), ensuring that all composite monofilaments are within the effective conductive region; ρ is the macroscopic fiber resistivity of single-walled carbon nanotubes in Ω·m; μ0 is the vacuum permeability in H / m; f is the alternating current frequency in Hz; and d1 is in meters (m).

[0082] In a specific embodiment of the present invention, for SWCNT macrofibers (ρ≈1×10⁻⁶), -7 The skin depth of the composite wire (Ω·m) is 1.6 mm at 10 kHz and 0.5 mm at 100 kHz. By controlling the diameter of the outermost composite filament, each composite filament is placed within the effective conductive region, thus structurally eliminating skin effect losses. In contrast, the skin depth of copper wire is only 0.66 mm at 10 kHz and only 0.21 mm at 100 kHz, and the skin effect leads to severe AC losses.

[0083] The "superconducting substitution" described in this invention refers to the fact that the ultimate current-carrying capacity of SWCNT macrofibers is on the order of magnitude close to the engineering current density of HTS, and it does not require a cryogenic cooling system. HTS has zero resistance and does not generate Joule heat during operation, while SWCNT macrofibers have finite resistance and generate significant Joule heat at operating current densities. The continuous operating current density of SWCNT macrofibers is much lower than its ultimate current-carrying capacity, subject to thermal management constraints. The operating current density has a square relationship with Joule heat loss, J = 20 A / mm. 2 The loss at that time is J=5A / mm 2 The weight advantage is 16 times that of copper windings. Taking a copper layer thickness of 2μm, an inner thermally conductive transition layer, an intermediate electrical insulation layer, and an outer heat-resistant protective layer with a total thickness of 23μm and a slot fill factor of 78% as an example, the comparison between weight advantage and loss level is shown in Table 1 below. In lightweight applications where 3-4 times the copper winding loss is acceptable, the total weight of the SWCNT-Cu winding can be reduced to 37-43% of that of the copper winding. The PVD copper plating solution increases the overall density due to the copper layer density, but at the same time, the conductivity is greatly improved, and significant weight reduction can still be achieved in application scenarios where higher losses are acceptable. The weight advantage under conditions of equal loss is limited.

[0084] Table 1 Comparison between weight advantage and loss level

[0085] This invention utilizes the excellent axial thermal conductivity of SWCNT macrofibers (100~500 W / m·K). The high current density single-walled carbon nanotube macrofiber superconducting alternative motor winding described in this invention serves as a self-heating channel. The end extensions of the high current density single-walled carbon nanotube macrofiber superconducting alternative motor winding (with 10~30 mm reserved at each end) preferably do not have an intermediate electrical insulation layer or an outer heat-resistant protective layer, retaining only an inner thermally conductive transition layer. The end extensions preferably directly contact the motor end heat dissipation structure (such as aluminum alloy heat sink fins or coolant channels). Joule heat inside the winding is preferably conducted to the end and dissipated through the high axial thermal conductivity of the SWCNT macrofibers, forming a self-heating path of "core layer axial heat conduction - end heat dissipation." The high current density single-walled carbon nanotube macrofiber superconducting alternative motor winding described in this invention operates at 3~5 A / mm. 2 It can achieve self-heating operation at operating current density of 5A / mm. 2 The Joule heat power density at that point is 1.67 × 10⁻⁶. 6 W / m 3 With copper at 10A / mm 2 1.72×10 6 W / m 3 It is comparable to copper, at 0.97 times the current density, and auxiliary air cooling or liquid cooling is preferred at higher current densities.

[0086] The high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding described in this invention can achieve a much higher limiting current carrying capacity than traditional copper windings at room temperature, with a limiting current carrying capacity of 300~500 A / mm². 2 That is, 3×10 8 ~5×10 8 A / m 2 With an engineering current density approaching that of high-temperature superconducting materials (on the order of magnitude), it can achieve significant weight reduction in applications where higher losses are acceptable. It does not require a cryogenic cooling system and can replace traditional copper windings and high-temperature superconducting (HTS) windings, providing a "superconducting alternative" lightweight winding solution for high-power-density motors. It is preferably used in aerospace motors, electric vehicle drive motors and other fields.

[0087] In this invention, the high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding is preferably embedded in the stator slot or wound on the rotor frame according to the motor winding drawing, and the end is fixed by epoxy resin casting. The end heat dissipation section is in contact with the heat dissipation structure of the motor housing for assembly.

[0088] The advantages of the high current density single-walled carbon nanotube macroscopic fiber superconducting replacement motor winding described in this invention compared with existing copper windings, HTS superconducting windings, and existing CNT wire technologies are shown in Table 2 below.

[0089] Table 2 Advantages of the present invention over the prior art

[0090] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0091] Example 1: High Power Density Motor Winding for Unmanned Aerial Vehicles Target parameters: Rated power 10kW, speed 20000rpm, operating frequency 3.3kHz, continuous operating current density 20A / mm² 2 (Under extremely high loss conditions, the Joule heat is approximately 10 A / mm² for copper) 2 The weight is 19 times that of copper windings (only applicable to short-duration high-power UAV scenarios equipped with powerful liquid cooling systems).

[0092] The preparation process includes the following steps: Step S1: Preparation of SWCNT macrofibers A liquid crystal wet spinning process was employed, in which SWCNT powder was dispersed in chlorosulfonic acid to form a liquid crystal phase spinning solution. This solution was then extruded through a porous spinneret into a coagulation bath, and circular cross-section fibers were obtained by controlling the double diffusion rate in the coagulation bath. After densification and traction in an air section, the fibers were washed with water until neutral, and then vacuum dried. The SWCNT powder purity was 97 wt%, with 0.3 wt% metal residue; the liquid crystal phase spinning solution concentration was 3.0 wt%; the coagulation bath was pure acetone solution; the spinning speed was 10 m / min; the diameter of the resulting macroscopic SWCNT fibers was 25 μm, and the fiber conductivity was 6.2 × 10⁻⁶. 6 S / m (before copper plating). Figure 3 The image shows a SEM image of the macroscopic SWCNT fibers obtained in Example 1.

[0093] Step S2: DC magnetron sputtering PVD copper plating treatment The SWCNT macrofibers obtained in step S1 were fixed onto the sample holder of a magnetron sputtering device. First, Ar ion cleaning was performed (bias voltage -100V, Ar flow rate 60sccm, 15min), followed by DC magnetron sputtering with a pure copper target (99.99%): working pressure 0.5Pa, DC power 150W, sample holder rotation 10rpm, deposition rate 100nm / min, copper layer thickness 2μm, Cu layer thickness 2μm / fiber radius 12.5μm = 16%, SWCNT macrofibers accounted for 74.3% of the conductive core volume, demonstrating significant lightweight advantages. After copper plating, annealing was performed at 400℃ for 30min in an Ar atmosphere to promote Cu-SWCNT interface diffusion and bonding. The effective conductivity after copper plating was 1.65×10⁻⁶. 7 S / m, stability (200℃×500h): conductivity decayed by 2.8%. Figure 4 This is a SEM image of the conductive core layer prepared in Example 1.

[0094] Step S3: Inner thermally conductive transition layer coating The BNNP / PAA composite slurry (BNNP content 20wt%) was dipped onto the surface of the fiber obtained in step S2, passed through the dip-coating mold at a linear speed of 20 mm / s, and cured at 300℃ for 30s to form an inner thermally conductive transition layer BNNP / PI with a thickness of 5 μm.

[0095] Step S4: Covering with intermediate electrical insulation layer A PI film (10 μm thick) is wrapped around the surface of the fiber obtained in step S3 with a 50% overlap.

[0096] Step S5: Coating the outer heat-resistant protective layer The nano-SiO2 / PAI coating (10wt% nano-SiO2 content) was applied to the surface of the fiber obtained in step S4 by mold coating and cured at 200℃ for 60s to form a protective layer with a thickness of 8μm, thus obtaining a composite monofilament.

[0097] Composite monofilament diameter: d1 = 25 + 2 × 2 + 2 × (5 + 10 + 8) = 75 μm (including 2 μm of PVD copper plating).

[0098] Step S6: First-stage twisting Take 19 composite monofilaments and twist them together on a tubular stranding machine with a twist pitch of 15d1 (d1 is the diameter of the composite monofilament) and a Z-direction twist to form primary strands with a diameter of 5d1 = 0.375 mm.

[0099] Step S7: Second-stage twisting Take 7 primary strands and twist them together on a cage stranding machine with a twist pitch of 12d2 (d2 is the diameter of the primary strand) and an S-direction twist to form a secondary cable with a diameter of 3d2 = 1.125 mm.

[0100] Step S8: Third-stage forming twisting Six secondary cables are taken and twisted together with a twist pitch of 20d3 (d3 is the diameter of the secondary cable) and a Z-direction twist direction. The diameter of the winding wire is 3d3 = 3.375mm. After twisting, the circular cross-section is pressed into a rectangular cross-section (width-to-thickness ratio 2:1) through a roll forming die. The rectangular cross-section has a size of 3.2mm × 1.6mm, resulting in the final winding wire.

[0101] Step S9: End Processing Cut the winding wires according to the design dimensions of the motor windings, leaving a 10mm uninsulated section at each end (removing the middle electrical insulation layer and the outer heat-resistant protective layer coating, while retaining the middle electrical insulation layer) as the end self-heating contact area.

[0102] Step S10: Winding insertion and fixing The winding wires obtained in step S8 are embedded into the stator slots or wound onto the rotor frame according to the motor winding drawings. The ends are fixed by epoxy resin casting, and the end heat dissipation section is in contact with the heat dissipation structure of the motor housing.

[0103] Performance parameters: Effective conductivity of winding wire (conductor cross-section reference): 1.2 × 10⁻⁶ 7 S / m (Conductivity after copper plating, considering stranded contact resistance, is 1.65 × 10⁻⁶) 7 (73% of S / m) Continuous operating current density: 20A / mm 2 (Conductor cross-section, under liquid cooling conditions; Joule heat power density P = 33.3 MW / m² at this current density) 3 For copper at 10A / mm 2 1.72MW / m 3 19.4 times that of drones, suitable for short-term high-power scenarios where weight is extremely sensitive and equipped with powerful liquid cooling systems. Ultimate current carrying capacity: 300A / mm 2 (Short-term peak); Winding weight: Under the same current capacity, the weight of the conductive core layer is 17% of that of the copper winding, and the total weight of the winding wire is 30% of that of the copper winding; Axial thermal conductivity: 380 W / m·K (through SWCNT core layer); Corona resistance life (PWM 400 V / dc, switching frequency 8kHz): 520h; Bending fatigue life (R=5d, 1000 bending cycles): resistance increases by 1.8%; End temperature rise: 20A / mm 2 The bottom requires powerful liquid cooling, and the end self-heating only plays an auxiliary role; the steady-state temperature rise under liquid cooling conditions is ≤120K.

[0104] Example 2: Target parameters: Rated power 150kW, speed 12000rpm, operating frequency approximately 1.0kHz, continuous operating current density 10A / mm² 2 (Joule heating for copper at 10 A / mm) 2 (5.1 times that of the previous year, requiring forced air cooling), the target winding weight is ≤ 55% of the copper winding weight.

[0105] The preparation process includes the following steps: Step S1: Preparation of SWCNT macrofibers A liquid crystal wet spinning process was employed, in which SWCNT powder was dispersed in chlorosulfonic acid to form a liquid crystal phase spinning solution. This solution was then extruded through a porous spinneret into a coagulation bath, and circular cross-section fibers were obtained by controlling the double diffusion rate in the coagulation bath. After densification and traction in an air section, the fibers were washed with water until neutral, and then vacuum dried. The SWCNT powder purity was 95 wt%, with 0.5 wt% metal residue; the liquid crystal phase spinning solution concentration was 3.0 wt%; the coagulation bath was pure acetone solution; the spinning speed was 10 m / min; the diameter of the resulting macroscopic SWCNT fibers was 35 μm, and the fiber conductivity was 5.5 × 10⁻⁶. 6 S / m (before copper plating).

[0106] Step S2: DC magnetron sputtering PVD copper plating treatment The macroscopic SWCNT fibers obtained in step S1 were fixed onto the sample holder of a magnetron sputtering device. First, Ar ion cleaning was performed (bias voltage -100V, Ar flow rate 60sccm, 15min). Then, DC magnetron sputtering was performed with a pure titanium target at a DC power of 80W and a deposition rate of 5nm / min, depositing a 30nm thick Ti interface transition layer. Next, DC magnetron sputtering was performed with a pure copper target (99.99%) at a working pressure of 0.5Pa, a DC power of 200W, a sample holder rotation of 15rpm, and a deposition rate of 120nm / min, resulting in a 3μm thick copper layer. The Cu layer thickness was 3μm / fiber radius 17.5μm = 17%, with the conductive core layer accounting for 72.6% of the conductor volume, demonstrating significant lightweight advantages. After copper plating, annealing was performed at 400℃ for 30min in an Ar atmosphere to promote Cu-SWCNT interface diffusion and bonding. The effective conductivity after copper plating was 1.55×10⁻⁶. 7 S / m, stability (200℃×500h): conductivity decayed by 3.2%.

[0107] Step S3: Inner thermally conductive transition layer coating An inner thermally conductive transition layer of 8 μm thickness, BNNP / PEEK composite material (BNNP content 15 wt%), was formed on the surface of the conductive core layer by extrusion.

[0108] Step S4: Covering with intermediate electrical insulation layer FEP extrusion coating was used, with an extrusion temperature of 380℃, a coating thickness of 20μm, and water-cooled curing.

[0109] Step S5: Coating the outer heat-resistant protective layer The nano-SiO2 / PAI coating (nano-SiO2 content 8wt%) was applied to the surface of the fiber obtained in step S4 by mold coating and cured at 200℃ for 60s to form a protective layer with a thickness of 10μm, thus obtaining a composite monofilament.

[0110] Composite monofilament diameter: d1=35+2×3+2×(8+20+10)=117μm (including 3μm of PVD copper plating).

[0111] Step S6: First-stage twisting Take 37 composite monofilaments and twist them together on a tubular stranding machine with a twist pitch of 15d1 (d1 is the diameter of the composite monofilament) and Z-direction twist to form primary strands with a diameter of 7d1 = 0.819 mm.

[0112] Step S7: Second-stage twisting Twelve primary strands are twisted together on a cage stranding machine with a twist pitch of 12d2 (d2 being the diameter of the primary strand) and an S-direction twist to form a secondary cable with a diameter of 2.9mm.

[0113] Step S8: Third-stage forming twisting Eight secondary cables are taken and twisted together with a twist pitch of 20d3 (d3 is the diameter of the secondary cable) and a Z-direction twist direction, resulting in a winding wire diameter of 7.8mm. After twisting, the circular cross-section is pressed into a rectangular cross-section (width-to-thickness ratio 1.48:1) using a roll forming die. The rectangular cross-section has dimensions of 8mm × 5.4mm, resulting in the final winding wire.

[0114] Step S9: End Processing Cut the winding wires according to the design dimensions of the motor windings, leaving a 10mm uninsulated section at each end (removing the middle electrical insulation layer and the outer heat-resistant protective layer coating, while retaining the middle electrical insulation layer) as the end self-heating contact area.

[0115] Step S10: Winding insertion and fixing The winding wires obtained in step S8 are embedded into the stator slots or wound onto the rotor frame according to the motor winding drawings. The ends are fixed by epoxy resin casting, and the end heat dissipation section is in contact with the heat dissipation structure of the motor housing.

[0116] Performance parameters: Continuous operating current density: 10A / mm 2 (Conductor cross-section, under forced air cooling conditions; Joule heat power density P = 8.85 MW / m² at this current density)3 For copper at 10A / mm 2 1.72MW / m 3 (5.1 times that of the previous generation, requiring forced air cooling). Ultimate current carrying capacity: 300A / mm 2 (Short-term peak); Winding weight: Under the same current capacity, the weight of the conductive core layer is 34% of that of the copper winding, and the total weight of the winding wire is 50% of that of the copper winding; Axial thermal conductivity: 380 W / m·K (through SWCNT core layer); Corona resistance life (PWM 400 V / dc, switching frequency 8kHz): 510h; Bending fatigue life (R=5d, 1000 bending cycles): resistance increases by 2.2%; Under continuous operation at 150kW, the winding steady-state temperature is ≤110℃ (under air-cooled conditions).

[0117] Example 3: Industrial high-power motor windings Target parameters: Rated power 500kW, speed 1500rpm, operating frequency 50Hz, continuous operating current density 5A / mm² 2 (Joule heating for copper at 10 A / mm) 2 (1.7 times that of the previous year, which can be naturally convection cooled), the winding weight target is ≤85% of the copper winding, emphasizing long-term reliability and cost control.

[0118] The preparation process includes the following steps: Step S1: Preparation of SWCNT macrofibers A liquid crystal wet spinning process was employed, in which SWCNT powder was dispersed in chlorosulfonic acid to form a liquid crystal phase spinning solution. This solution was then extruded into a coagulation bath through a porous spinneret. Circular cross-section fibers were obtained by controlling the double diffusion rate in the coagulation bath. After densification and traction in an air section, the fibers were washed with water until neutral and then vacuum dried. The SWCNT powder purity was 93 wt%, with 0.8 wt% metal residue; the liquid crystal phase spinning solution concentration was 3.0 wt%; the coagulation bath was pure acetone solution; the spinning speed was 10 m / min; the diameter of the resulting macroscopic SWCNT fibers was 50 μm, and the fiber conductivity was 4.8 × 10⁻⁶. 6 S / m (before copper plating).

[0119] Step S2: DC magnetron sputtering PVD copper plating treatment The macroscopic SWCNT fibers obtained in step S1 were fixed onto the sample holder of a magnetron sputtering device. First, Ar ion cleaning was performed (bias voltage -100V, Ar flow rate 60sccm, 15min), followed by DC magnetron sputtering with a pure copper target (99.99%): working pressure 0.5Pa, DC power 100W, sample holder rotation 5rpm, deposition rate 120nm / min, copper layer thickness 1.5μm, Cu layer thickness 1.5μm / fiber radius 25μm = 6%, conductive core layer accounting for 89% of conductor volume, demonstrating significant lightweight advantages. After copper plating, annealing was performed at 350℃ for 40min in an Ar atmosphere to promote Cu-SWCNT interface diffusion and bonding. Effective conductivity after copper plating: 1.2×10⁻⁶ 7 S / m, stability (200℃×500h): conductivity decayed by 4.5%.

[0120] Step S3: Inner thermally conductive transition layer coating The BNNP / PAA composite slurry (BNNP content 10wt%) was dipped onto the surface of the fiber obtained in step S2, passed through the dip coating mold at a linear speed of 20mm / s, and cured at 300℃ for 30s to form an inner thermally conductive transition layer BNNP / PI with a thickness of 10μm.

[0121] Step S4: Covering with intermediate electrical insulation layer A PI film (15 μm thick) was wrapped around the surface of the fiber obtained in step S3 with a 50% overlap rate, and then FEP was used for extrusion coating at a temperature of 380℃ and a coating thickness of 10 μm, followed by water-cooled curing.

[0122] Step S5: Coating the outer heat-resistant protective layer A 12 μm thick protective layer was formed on the surface of the intermediate electrical insulation layer using a BNNP / PEEK composite material (BNNP content 15 wt%) through extrusion to obtain a composite monofilament.

[0123] Composite monofilament diameter: d1 = 50 + 2 × 1.5 + 2 × (10 + 15 + 10 + 12) = 147 μm (including 1.5 μm of PVD copper plating).

[0124] Step S6: First-stage twisting Take 19 composite monofilaments and twist them together on a tubular stranding machine with a twist pitch of 15d1 (d1 is the diameter of the composite monofilament) and Z-direction twist to form primary strands with a diameter of 5d1 = 0.735 mm.

[0125] Step S7: Second-stage twisting Take 19 primary strands and twist them together on a cage stranding machine with a twist pitch of 12d2 (d2 is the diameter of the primary strand) and an S-direction twist to form a secondary cable with a diameter of 3.7mm.

[0126] Step S8: Third-stage forming twisting Twelve secondary cables are taken and twisted together with a twist pitch of 20d3 (d3 is the diameter of the secondary cable) and a Z-direction twist direction, resulting in a winding diameter of 11.1 mm. After twisting, the circular cross-section is pressed into a rectangular cross-section (width-to-thickness ratio 1.49:1) using a roll forming die. The rectangular cross-section has dimensions of 11 mm × 7.4 mm, resulting in the final winding wire.

[0127] Step S9: End Processing Cut the winding wires according to the design dimensions of the motor windings, leaving a 10mm uninsulated section at each end (removing the middle electrical insulation layer and the outer heat-resistant protective layer coating, while retaining the middle electrical insulation layer) as the end self-heating contact area.

[0128] Step S10: Winding and fixing The winding wires obtained in step S8 are embedded into the stator slots or wound onto the rotor frame according to the motor winding drawings. The ends are fixed by epoxy resin casting, and the end heat dissipation section is in contact with the heat dissipation structure of the motor housing.

[0129] Performance parameters: Continuous operating current density: 5A / mm 2 (Conductor cross-section, under natural convection cooling conditions); Ultimate current carrying capacity: 300A / mm 2 (Short-term peak); Winding weight: Under the same current capacity, the weight of the conductive core layer is 67% of that of the copper winding, and the total weight of the winding wire is 85% of that of the copper winding; Axial thermal conductivity: 300 W / m·K (through SWCNT core layer); Corona resistance life (PWM 400 V / dc, switching frequency 8kHz): conductivity decreases by 4.8% after 20,000 hours of aging; Under continuous 150kW operating conditions, the winding steady-state temperature is ≤95℃ (natural convection cooling). Bending fatigue life (R=5d 1000 bending cycles): Resistance increases by 3.0%.

[0130] Comparative Example 1: Preparation of SWCNT / polymer composite winding wire by direct blending method Composite wires were prepared by directly blending and extruding SWCNT powder with PEEK, with an SWCNT content of 30 wt%.

[0131] Electrical conductivity: only 2.1 × 10⁻⁶ 4 S / m (three orders of magnitude lower than that of this invention); Current density: <1A / mm 2 (Unable to meet motor requirements); Reason: SWCNTs are randomly dispersed in the polymer matrix, resulting in extremely high inter-tube contact resistance and complete loss of ballistic transport characteristics; Conclusion: Direct blending cannot achieve the conductivity advantage of SWCNTs. The macro-fiber spinning + multi-stage stranding method of this invention is a necessary condition for achieving high current density.

[0132] Comparative Example 2: Single-stage stranded SWCNT fiber winding Similar to Example 1, the only difference is that a single-stage simple twisting (19 SWCNT composite monofilaments directly twisted together) is used, without multi-stage twisting and forming processes, to obtain a circular cross-section.

[0133] AC loss at 10kHz: 3.5 times that of the multi-stage stranded structure of this invention; Slot fill factor: only 58% (circular cross-section, not roll-formed), lower than Example 1; Bending fatigue life (R=5d 1000 bending cycles): resistance increased by 12%, higher than in Example 1; Conclusion: The multi-stage stranding structure and molding process significantly contribute to high-frequency performance, slot fill factor, and mechanical reliability.

[0134] Comparative Example 3: Bare SWCNT fiber windings without PVD copper plating Similar to Example 1, except that the same SWCNT fibers are used but without PVD copper plating, and the windings are directly prepared.

[0135] Macroscopic fiber effective electrical conductivity: 6.2 × 10⁻⁶ 6 S / m (compared to 1.65 × 10⁻⁶ after copper plating in Example 1 of this invention) 7 S / m is 62% lower (compared to S / m). Fiber-terminal contact resistance: Under the same terminal, crimping force and effective length conditions, the bare SWCNT fiber has a resistance of 32.0 mΩ, while the CNT-Cu core-shell fiber of Example 1 of this invention has a resistance of 4.8 mΩ. The former is 6.7 times that of the latter, indicating that the copper layer significantly improves the surface electrical contact. After 200℃ for 500 hours, fiber surface oxidation resulted in an electrical conductivity of 4.1 × 10⁻⁶. 6 S / m, attenuation 34%, in Example 1 of the present invention, after 200℃×500h, the conductivity decreased by 2.8% (copper plating protective effect). Environmental durability: The conductivity of bare SWCNT fibers decreased by 52% after 1000 hours in a humid and hot environment (85℃ / 85%RH), while that of copper-plated fibers in Example 1 of this invention decreased by 7.5%. Conclusion: The PVD copper plating not only provides enhanced conductivity but also plays a crucial role in protecting the SWCNT core layer from oxidation and environmental corrosion, making it an essential structure for ensuring the long-term reliability of motor operation.

[0136] Comparative Example 4: Cu layer thickness 10 μm Same as Example 1, except that the Cu layer thickness is 10 μm, and the Cu layer thickness of 10 μm / fiber radius of 12.5 μm = 80%.

[0137] The performance test comparisons of Example 1 and Comparative Example 4 are shown in Table 3. It can be seen that the Cu layer thickness should not be too high and should not exceed 50% of the macroscopic fiber radius of SWCNT.

[0138] Table 3 Performance test comparison between Example 1 and Comparative Example 4

[0139] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A composite monofilament, characterized in that, From the inside out, it includes a conductive core layer, an inner thermally conductive transition layer, an intermediate electrical insulating layer, and an outer heat-resistant protective layer. The conductive core layer has a core-shell structure, with a single-walled carbon nanotube macrofiber as the core and a copper layer as the shell.

2. The composite monofilament according to claim 1, characterized in that, An interface transition layer is also provided between the macroscopic fibers of the single-walled carbon nanotubes and the copper layer, and the material of the interface transition layer includes Ti and / or Al.

3. The composite monofilament according to claim 1, characterized in that, The inner thermally conductive transition layer includes a thermally conductive substrate and a thermally conductive filler, wherein the content of the thermally conductive filler in the inner thermally conductive transition layer is 10~30wt%.

4. The composite monofilament according to claim 1, characterized in that, The intermediate electrical insulating layer comprises polyimide and / or fluorinated ethylene propylene copolymer.

5. The composite monofilament according to claim 1, characterized in that, The outer heat-resistant protective layer is a polyamide-imide layer containing silicon dioxide or a polyether ether ketone layer containing boron nitride.

6. The method for preparing the composite monofilament according to any one of claims 1 to 5, characterized in that, Includes the following steps: Provides macroscopic fibers of single-walled carbon nanotubes; Physical vapor deposition is performed on the surface of the single-walled carbon nanotube macrofiber to form the copper layer, thus obtaining the conductive core layer. The conductive core layer is sequentially combined with an inner thermally conductive transition layer, an intermediate electrical insulating layer, and an outer heat-resistant protective layer to obtain the composite monofilament.

7. The application of the composite monofilament as described in any one of claims 1 to 5 or the composite monofilament prepared by the preparation method described in claim 6 as a conductive material in the field of motors.

8. A high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding, characterized in that, The composite monofilament obtained by the composite monofilament according to any one of claims 1 to 5 or by the preparation method according to claim 6 is formed by multi-stage twisting, wherein the number of twisting stages is ≥2 and the twisting directions of adjacent stages are opposite.

9. The high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding according to claim 8, characterized in that, The number of twist levels in the multi-stage twisting is 3.

10. The high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding according to claim 8, characterized in that, The diameter d1 of the outermost composite filament of the high current density single-walled carbon nanotube macroscopic fiber superconducting alternative motor winding satisfies Formula 1: Official 1; Where δ is the skin depth in meters (m), ρ is the macroscopic fiber resistivity of single-walled carbon nanotubes in Ω·m, μ0 is the vacuum permeability in H / m, f is the alternating current frequency in Hz, and d1 is in meters (m).